Learning Science Based on Socio-Scientific Issue: Batik Waste in Jetis Sidoarjo: Belajar IPA Berbasis Socio-Scientific Issue: Limbah Batik Jetis Sidoarjo - Siti Adira Salsabilla Rahma; Ria Wulandari (Universitas Muhammadiyah Sidoarjo, 2025)
This study presents the development of a science learning e-book integrating socio-scientific issues within environmental education. General Background: Digital learning resources such as interactive e-books have become increasingly significant in supporting science education in the digital era. Specific Background: Integrating Socio-Scientific Issue (SSI) approaches into science learning enables students to connect scientific concepts with real environmental problems, including batik waste pollution in Jetis Sidoarjo. Knowledge Gap: However, limited digital learning media contextualize local environmental issues within Phase D science curriculum content while systematically promoting higher-order thinking skills. Aims: This study aims to develop an SSI-based science e-book that links environmental pollution and interactions among living organisms with the contextual issue of batik waste. Results: The developed e-book consists of structured materials, issue analysis, observation and evaluation activities, quizzes, reflective tasks, and final projects designed to foster HOTS indicators C4 and C5, supported by interactive navigation and visual communication design. Novelty: The novelty lies in the integration of local batik waste issues into an interactive digital format aligned with the curriculum. Implications: The e-book serves as a supplementary science learning resource that promotes contextual understanding and active student engagement in environmental problem solving. Keywords: Science Learning E-Book, Socio-Scientific Issue, Batik Waste Pollution, Higher-Order Thinking Skills, Environmental Education Key Findngs Highlights: Interactive digital material connects environmental pollution topics with local batik waste cases. Structured analytical and evaluative activities facilitate advanced cognitive processes. Contextual project tasks encourage solution-oriented reasoning in science classes.